Iodothyronine deiodinase 2 (DiO2) regulates trophoblast cell line cycle, invasion and apoptosis; and its downregulation is associated with early recurrent miscarriage. (August 2021) - Adu-Gyamfi, Enoch Appiah; Lamptey, Jones; Chen, Xue-Mei; Li, Fang-Fang; Li, Cong; Ruan, Ling-Ling; Yang, Xue-Niu; Liu, Tai-Hang; Wang, Ying-Xiong; Ding, Yu-Bin
Abstract: Introduction: Trophoblast development is a crucial event in placentation and pregnancy complications but its underlying mechanisms remain unclear. Thus, we aimed at investigating the role of DiO2 in trophoblast cell line decisions and assessing its placental villous expression in early recurrent miscarriage (ERM) patients. Methods: The placental villous expression of DiO2 was determined with immunofluorescence. Cell proliferation was measured with the CCK8 kit while cell-cycle and apoptosis were studied with flow-cytometry. Cell migration and invasion were measured with wound-healing and transwell assays, respectively. Gene expression was then assessed with RT-qPCR and western blotting. Results: DiO2 is expressed in the CTB, PCT, DCT and STB of the placenta. Its overexpression arrested trophoblast cell line proliferation at the G1 phase of the cell-cycle by downregulating cyclin-D1 and PCNA, while promoting apoptosis via increased caspase-3 activity and inhibition of the AKT and ERK1/2 signaling pathways. Also, it augmented trophoblast cell line migration and invasion via the upregulation of N-cadherin, vimentin, fascin-1, twist-1 and other epithelial-mesenchymal transition genes. DiO2 knockdown elicited the opposite effects. Surprisingly, each of these effects of DiO2 manipulation was not mediated by thyroid hormone metabolism. Assessment of the ERM placental villi revealed a downregulation of DiO2, N-cadherin, vimentin, fascin-1 and twist-1. The expression of E-cadherin remained unchanged in these placentae. Discussion: During placentation, DiO2 may inhibit trophoblast proliferation while facilitating their differentiation into an invasive phenotype; and that its downregulation may contribute to the shallow trophoblast invasion that precedes ERM. Hence, DiO2 is a potential therapeutic target against ERM. Highlights: DiO2 is highly expressed in the first trimester placental villi. DiO2 can regulate cellular activities without acting on thyroid hormones. Downregulation of DiO2 in the first trimester placental villi is involved in the pathogenesis of early recurrent miscarriage.